Leadership that gets results - Goleman, Daniel (Boston HBR, 2017)
A leader's singular job is to get results. But even with all the leadership training programs and "expert" advice available, effective leadership still eludes many people and organizations. One reason, says Daniel Goleman, is that such experts offer advice based on inference, experience, and instinct, not on quantitative data. Now, drawing on research of more than 3,000 executives, Goleman explores which precise leadership behaviors yield positive results. He outlines six distinct leadership styles, each one springing from different components of emotional intelligence. Each style has a distinct effect on the working atmosphere of a company, division, or team, and, in turn, on its financial performance. Coercive leaders demand immediate compliance. Authoritative leaders mobilize people toward a vision. Affiliative leaders create emotional bonds and harmony. Democratic leaders build consensus through participation. Pacesetting leaders expect excellence and self-direction. And coaching leaders develop people for the future. The research indicates that leaders who get the best results don't rely on just one leadership style; they use most of the styles in any given week. Goleman details the types of business situations each style is best suited for, and he explains how leaders who lack one or more of these styles can expand their repertories. He maintains that with practice leaders can switch among leadership styles to produce powerful results, thus turning the art of leadership into a science.
Keywords: Leadership